2005
DOI: 10.1890/05-0486
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Model Investigation of Invasive Species Control: Bullfrogs on Vancouver Island

Abstract: Invasive species control is now a conservation priority in many parts of the world. Demographic modeling using population matrix models is a useful tool in the design of these control efforts as it identifies the life stages with the strongest influence on population dynamics. As a case in point, American bullfrogs (Rana catesbeiana) have been introduced around the world and have negative effects on native fauna. We studied demography of four populations on southern Vancouver Island, Canada, using field observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
105
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 55 publications
1
105
2
Order By: Relevance
“…In contrast to recruitment limitation, regulation by density dependent factors (competition and predation) appears to be a dominant process for many amphibian populations, especially lentic associated species (Biek et al 2002;Govindarajulu et al 2005;Vonesh and De la Cruz 2002). Some experiments have shown that egg mortality is compensated for when surviving larvae are released from competition resulting in the similar number of individuals reaching metamorphosis (Skelly and Kiesecker 2001).…”
Section: Discussion-recruitment Limitation Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to recruitment limitation, regulation by density dependent factors (competition and predation) appears to be a dominant process for many amphibian populations, especially lentic associated species (Biek et al 2002;Govindarajulu et al 2005;Vonesh and De la Cruz 2002). Some experiments have shown that egg mortality is compensated for when surviving larvae are released from competition resulting in the similar number of individuals reaching metamorphosis (Skelly and Kiesecker 2001).…”
Section: Discussion-recruitment Limitation Hypothesismentioning
confidence: 99%
“…Previous studies have shown that larval growth and development rates are correlated with components of adult fitness (Smith 1987;Semlitsch et al 1988;Berven 1990) and are important demographic factors in influencing overall population growth rate (Govindarajulu et al 2005). For other ranid frogs, the larval growth environment has been shown to influence postmetamorphic chance of survival, and time to sexual maturity (Altwegg and Reyer 2003).…”
Section: Conclusion From Tadpole Experimentsmentioning
confidence: 99%
“…Such a strategy may have additional benefits in a species with overwintering larvae, such as Alytes obstetricans. If warmer water speeds up development such that fewer tadpoles hibernate (Thiesmeier, 1992), then population growth rate is predicted to increase (Govindarajulu, Altwegg and Anholt, 2005). If this reasoning is correct, then warmer ponds may be beneficial for amphibians because Bd prevalence may be lower and population growth rate higher.…”
mentioning
confidence: 99%
“…Kosior and Wandzel 2001, 13. Smith et al 1996 Three potential causes of overcompensation in response to harvest are increases in adult reproduction rates, juvenile survival rates, and juvenile maturation rates (Govindarajulu et al 2005, De Roos et al 2007). An increase in adult reproduction can result if harvest efforts reduce adult competition or otherwise increase resource availability.…”
Section: Introductionmentioning
confidence: 99%
“…Given that harvest efforts to manage invasive species focus on the target species, reductions in juvenile predation pressure as a response to removal efforts will only occur in populations that exhibit cannibalism. Cannibalism was the main driver of overcompensation in laboratory cultures of the flour beetle Tribolium (Dennis et al 1997) and is a potential driver of overcompensation in bullfrog populations (Govindarajulu et al 2005). Given that cannibalism has been observed among juvenile Carcinus and is common for brachyuran crabs, the infra-order to which Carcinus belongs, adult impacts on juvenile mortality may set the stage for overcompensation (Hines & Ruiz 1995, Moksnes et al 1997, Moksnes 2004).…”
Section: Introductionmentioning
confidence: 99%